Graphene oxide/chitosan nanocomposite coated quartz crystal microbalance sensor for detection of amine vapors - Zhang, Kaihuan; Hu, Ruifen; Fan, Guokang; Li, Guang (Sensors and actuators. B, Chemical, 2017)
•Graphene oxide/chitosan (GO/CS) nanocomposite prepared with a facile approach was used as the sensing material for a QCM sensor.•The QCM sensor based on the GO/CS nanocomposite provided a highly selective method for sensitive amine vapor detection.•The combination of CS and GO improved the sensor performances significantly in comparison with individual GO and CS. Graphene oxide/chitosan (GO/CS) nanocomposite was synthesized using a facile method and employed as the sensing material of a quartz crystal microbalance (QCM) sensor to detect amine vapors. Scanning election microscopy (SEM), Fourier transform infrared spectrometer (FT-IR) and UV–visible spectra analysis were performed to characterize the morphology and physicochemical properties of the nanocomposite. The GO/CS obtained was in a porous mesh structure composed of interconnected nanofibers with diameters of approximately 50nm. A GO/CS functionalized QCM sensor was fabricated and its sensing properties were investigated. Being tested at room temperature, the sensor exhibited high sensitivity to aliphatic amines including methylamine (MA), dimethylamine (DMA) and trimethylamine (TMA), with the sensitivity values of 2.7, 2.3 and 4.8Hz/ppm, respectively. Their detection limits were all below 3ppm. The sensor maintained reasonable reversibility, repeatability as well as long-term stability. Combining the specific adsorption properties of chitosan (CS) with some inherent properties of graphene oxide (GO), the GO/CS coated sensor also performed favorable selectivity, especially for MA, DMA and TMA. The sensing mechanism might involve an adsorption–desorption process mainly caused by hydrogen bonding of the protonated amine and hydroxyl sites of the GO/CS film with the amine vapors. The underlying analyte sorption properties were further investigated based on the linear solvation energy relationship (LSER) model. This work might contribute to the future development of sensors for detection of amine vapors and broaden the application of GO and CS composite materials.